Unlocking mobile health adoption: A qualitative exploration of user experiences, barriers, and facilitators within integrated youth services in British Columbia, Canada - Xiaoxu Ding; Kirsten Marchand; Liisa Holsti; Julia Schmidt; Natalie Parde; Brodie Sakakibara; Skye Barbic (Digital Health, 2025)
Background Early onset of mental health disorders is common, but many cases remain undetected and untreated, highlighting the need for early intervention. In Canada, youth mental health services face challenges, including fragmentation and resource limitations. Integrated youth services (IYS) aim to address these gaps for individuals aged 12–24 years. Mobile health (mHealth) programs, like Foundry Virtual BC, offer potential solutions, yet their integration and sustainability within IYS require further exploration. Objective This study examined interest-holder perspectives on creating a sustainable, youth-centred mHealth system to improve mental health outcomes. The research focused on three questions: (a) How do users, service providers, and nonclinical staff perceive mHealth's effectiveness and impact? (b) What are the barriers and facilitators to mHealth integration within the Foundry IYS network? and (c) What strategies support the sustainability of mHealth services? Methods A qualitative study using semi-structured interviews was conducted with 23 interest-holders, including youth users, service providers, and nonclinical staff from the Foundry network. Participants were recruited via social media and snowball sampling. Thematic analysis identified key themes and subthemes. Results Three themes emerged regarding mHealth perceptions: (a) its own value, (b) its potential to address barriers to in-person care, and (c) its inherent limitations. Barriers and facilitators of mHealth integration were categorized into three domains: (a) design characteristics (e.g., app usability and content quality), (b) individual youth factors (e.g., privacy concern and inner struggle), and (c) external factors (e.g., safe space and support from peers). Sustainability was linked to service quality and external support. Conclusion This study highlights the complexity of mHealth integration within an IYS network. Interest-holders emphasized addressing user motivations, privacy, and accessibility while advocating for co-design approaches to ensure mHealth meets diverse youth needs. Future research should focus on underrepresented groups to promote equity and improve mental health outcomes through sustainable mHealth solutions.